The Role of User Training in the Adoption of ERMS in Institutions within the Framework of the Integrated Technology Acceptance and Usage Theory: A Foundation University Example - Eroğlu, Şahika; Kaya, Simge (Information World, 2025)
The purpose of this study is to analyse the role of user training in the adoption of the Electronic Record Management System (ERMS) used at a foundation university within the framework of the Unified Theory of Acceptance and Use of Technology (UTAUT). In this context, the levels of ERMS adoption among institutional employees were measured before and after training. In the study, the UTAUT scale developed by Venkatesh et al. (2003) was adapted, and users’ levels of adoption of the system were evaluated based on seven factors. In this quantitative research approach, data were collected through a survey; data obtained from 52 participants selected through stratified sampling were analyzed using descriptive statistics and statistical tests. The findings revealed a statistically significant relationship between user training and the level of adoption of the ERMS. It was observed that participants felt a need for regular training despite having existing knowledge about the ERMS. Based on the findings and literature, it is recommended that user training tailored to the target audience and their needs be continuously planned to ensure the effective adoption of the ERMS at the institutional level.
Keywords: Technology acceptance model; Unified theory of acceptance and use of technology; electronic records management systems; ERMS; user training